2019
DOI: 10.14260/jemds/2019/261
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphics and Intelligence Quotient (Iq) in Children of the Age Group 4 to 7 Years in the South Indian Population

Abstract: BACKGROUND Dermatoglyphics is considered to be a window to a child's personal characteristics and a sensitive indicator of brain function abnormalities. Widespread interest in epidermal ridges is developing in the medical field. In this study, certain specific patterns were prominent in high, intermediate and low IQ groups which were characteristic of these groups. METHODS This cross-sectional study was conducted on 1000 school going children in the South Indian population. Hand prints were taken using the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…In this study, a correlation was found between fingerprint patterns and IQ of Vietnamese students, students with whorls fingerprint patterns had a higher IQ than students with loop arches fingerprint patterns. (Prabhakaran et al, 2019) reported, the majority of the pupils in the high IQ group exhibited loop patterns. The patterns of arches and whorls were substantially more prevalent in the group of people with medium and low intellect.…”
Section: )mentioning
confidence: 87%
“…In this study, a correlation was found between fingerprint patterns and IQ of Vietnamese students, students with whorls fingerprint patterns had a higher IQ than students with loop arches fingerprint patterns. (Prabhakaran et al, 2019) reported, the majority of the pupils in the high IQ group exhibited loop patterns. The patterns of arches and whorls were substantially more prevalent in the group of people with medium and low intellect.…”
Section: )mentioning
confidence: 87%